2008
DOI: 10.1016/j.jmb.2008.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM Structure of Dodecameric Vps4p and Its 2:1 Complex with Vta1p

Abstract: The type I AAA ATPase Vps4 and its co-factor Vta1p/LIP5 function in membrane remodeling events that accompany cytokinesis, multivesicular body biogenesis, and retrovirus budding, apparently by driving disassembly and recycling of membrane-associated ESCRT-III complexes. Here, we present cryo-EM reconstructions of dodecameric yeast Vps4p complexes with and without their MIT Nterminal domains and Vta1p co-factors. The ATPase domains of Vps4p form a bowl-like structure composed of stacked hexameric rings. The two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
99
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 84 publications
8
99
0
Order By: Relevance
“…A model has also been proposed for ESCRT disassembly: it has been suggested that individual subunits are 'pumped' through the central pore of the VPS4 complex into the cytoplasm (Scott et al, 2005a;Stuchell-Brereton et al, 2007;Yu et al, 2008). In line with the mechanism of function for spastin, another MIT-domaincontaining AAA-ATPase (Roll-Mecak and Vale, 2008;White et al, 2007), the ESCRT-III subunits could be moved to binding sites within the central pore of the AAA-ATPase ring Shim et al, 2008), before being 'pulled' through via conformational changes induced during ATP binding and hydrolysis.…”
Section: A Membrane-deformation and -Scission Machinerymentioning
confidence: 99%
See 1 more Smart Citation
“…A model has also been proposed for ESCRT disassembly: it has been suggested that individual subunits are 'pumped' through the central pore of the VPS4 complex into the cytoplasm (Scott et al, 2005a;Stuchell-Brereton et al, 2007;Yu et al, 2008). In line with the mechanism of function for spastin, another MIT-domaincontaining AAA-ATPase (Roll-Mecak and Vale, 2008;White et al, 2007), the ESCRT-III subunits could be moved to binding sites within the central pore of the AAA-ATPase ring Shim et al, 2008), before being 'pulled' through via conformational changes induced during ATP binding and hydrolysis.…”
Section: A Membrane-deformation and -Scission Machinerymentioning
confidence: 99%
“…VPS4 enzymes form oligomeric complexes on endosomal membranes (Babst et al, 1998;Scott et al, 2005a); these complexes are comprised of two hexameric (Yu et al, 2008) or heptameric (Hartmann et al, 2008) rings. In yeast, Vta1 (human LIP5) stimulates the ATPase activity of Vps4 (Azmi et al, 2006;Lottridge et al, 2006) and promotes the assembly of the double ring structure (Xiao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These studies came to different conclusions with regard to the number of subunits present and the arrangement of these subunits within the complex. However, two of these studies concluded that the Vps4 oligomer is composed of two hexameric rings stacked tail-totail on top of each other (9,10). Furthermore, both studies observed that the two rings differed in their conformation, suggesting different functionalities for the two rings.…”
mentioning
confidence: 99%
“…Importantly, the role of Vps4 is conserved in all biological processes that depend on the action of the ESCRTs. Similar to other AAA-ATPases, Vps4 functions as an oligomer whose structure likely contains two conformationally distinctive hexameric rings (17). The rings contain a central pore where ESCRT-III subunits may physically interact and pass through during the disassembly process.…”
mentioning
confidence: 99%